The study of progesterone action in human myometrial explants - Georgiou, E.X.; Lei, K.; Lai, P.F.; Yulia, A.; Herbert, B.R.; Castellanos, Marcos; May, Sean; Sooranna, S.R.; Johnson, M.R. (Oxford University Press, 2016)
Study hypothesis: Myometrial explants represent a superior model compared with cell culture models for the study of human myometrial progesterone (P4) signalling in parturition. Study finding: Gene expression analysis showed myometrial explants closely resemble the in vivo condition and the anti-inflammatory action of P4 is not lost with labour onset. What is known already: Circulating P4 levels decline before the onset of parturition in most animals, but not in humans. This has led to the suggestion that there is a functional withdrawal of P4 action at the myometrial level prior to labour onset. However, to date, no evidence of a loss of P4 function has been provided, with studies hampered by a lack of a physiologically relevant model. Study design, samples/materials, methods: Myometrial biopsies obtained at Caesarean section were dissected into explants after a portion was immediately snap frozen (t = 0). Microarray analysis was used to compare gene expression of t = 0 with paired (i) explants, (ii) passage 4 myometrial cell cultures or (iii) the hTERT myometrial cell line. Western blotting and chemokine/cytokine assays were used to study P4 signalling in myometrial explants. Main results and the role of chance: Gene expression comparison of t = 0 to the three models demonstrated that explants more closely resemble the in vivo status. At the protein level, explants maintain both P4 receptor (PR) and glucocorticoid receptor (GR) levels versus t = 0 whereas cells only maintain GR levels. Additionally, treatment with 1 μM P4 led to a reduction in interleukin-1 (IL-1) β-driven cyclooxygenase-2 in explants but not in cells. P4 signalling in explants was PR-mediated and associated with a repression of p65 and c-Jun phosphorylation. Furthermore, the anti-inflammatory action of P4 was maintained after labour onset. Limitations/reasons for caution: There is evidence of basal inflammation in the myometrial explant model. Wider implications of the findings: Myometrial explants constitute a novel model to study P4 signalling in the myometrium and can be used to further elucidate the mechanisms of P4 action in human labour. Large scale data: Data deposited at http://www.ncbi.nlm.nih.gov/geo/query/acc.cgi?token=gvmpggkurbgxfqf&acc=GSE77830.